The patient experience movement moves on - Jason Wolf (The Beryl Institute, 2015)
As we present Volume 2 of Patient Experience Journal (PXJ) we both recognize the contributions that helped launch this publication and acknowledge the work that helped build the foundation of the broader research exploration in the emerging field of patient experience. On this base of knowledge we have worked to establish a new home for expanding the exploration of new ideas and practices through this publication. The importance of building, supporting and sustaining an outlet for research in patient experience is grounded in the belief that positive patient experience is good for healthcare, it is good for the people who comprise it and it should be of greatest benefit for those who are cared for and served. If we do our work as scholars and practitioners, in linking new ideas and solid proven practice, we have the potential to profoundly change the nature of healthcare. It is why we ask you as readers and researchers to continue to push the boundaries of what we believe is possible; understanding that at the end of the day, there is not only great opportunity, but great responsibility in focusing on excellence in patient experience and continuing to ensure the patient experience movement moves on.